Contested Children's Literature: Que(e)ries into Chicana and Central American Autofantasias - Millan, Isabel (My University, 2016)
This article takes seriously the political resilience and relevance of children’s literature produced by Chicanas and Centroaméricanas. I compare Honduran author Melissa Cardoza’s children’s book Tengo una tía que no es monjita (I have an aunt who is not a little nun) (Mexico, 2004) with Chicana author Gloria Anzaldúa’s children’s bookFriends from the Other Side/Amigos del Otro Lado (United States, 1993). The first text introduces readers to Meli, an eight-year-old girl who discovers her aunt’s romantic relationship with another woman. This narrative is intertwined with numerous subplots, including a critique of US neoliberalism and children’s entertainment. In the second text readers meet Prietita, a Chicana who befriends Joaquín, an undocumented boy. Throughout the story, Prietita and Joaquín tackle peer bullying and hide from border patrol agents. My analysis of each text prioritizes the authors’ use of autobiographical material alongside the texts’ narrative arcs and intended audiences. Both Anzaldúa and Cardoza engage in what I term autofantasía, a literary technique incorporating elements of autobiography and fantasy fiction writing, in order to model responses to xenophobia and queerphobia, or xeno/queerphobia.
Citation: Millan, I. (2015). Contested Children's Literature: Que(e)ries into Chicana and Central American Autofantasias. Signs, 41(1), 199-224. doi:10.1086/681919
Keywords: Women's Studies